Inflation and Consumer Basket - Popov, Vladimir A. (Journal of Reviews on Global Economics, 2018)
Formation of consumer basket is investigated by means of probability theory. Inflation on the consumer market can be managed by reducing its rate and lowering inflation-related risks. The approach is based on the treating the inflation risks of particular ingredients of the consumer goods basket as component of the whole complex rather than separate units. The proposed management strategy is focused on the degree of correlation between the rates of price increase of the items in the basket. Portfolio theories of Markowitz and Tobin are used.